'Green firecrackers' with reduced barium emissions in particulate matter. (15th January 2023) - Wankhede, Utkarsha; Khaparde, V.V.; Balpande, Krutika; Shinde, V.M.; Rayalu, Sadhana
Abstract: Ambient air quality is affected due to the emission of pollutants on a large scale after the bursting of firecrackers. Traditionally in all firecrackers, barium (Ba) compounds are used as oxidizers and also to impart green colour flame. Combustion products of barium compounds are water soluble and readily absorbed by the body affecting human health. Thus, the inherent risk of Ba pollution due to the bursting of firecrackers has consequent health effects. To reduce the ambient air pollution caused due to burning of conventional firecrackers, CSIR NEERI has developed reduced emission firecrackers (green crackers). This is achieved by reducing the amount of chemicals, barium nitrate, shell size and addition of additives such as zeolite and iron oxide. This study aims to specifically investigate the influence of additives on the level of barium in reduced emission firecrackers. Four types of conventional and reduced emission firecrackers were selected and tested inside a firecracker emission testing facility to check the levels of barium in PM10 and PM2.5 . The measured mean concentrations of all types of reduced emission crackers (green crackers) provided by fireworks manufacturers show significantly reduced barium concentration by 30–60% compared to conventional crackers depending on the type of firecrackers, shell size and amount of chemicals used. The possible reason for reduced Ba level is attributed to i) reduced usage of Ba(NO3 )2 and ii) formation of heavy density compounds, leading to soil fallout. Graphical abstract: Image 1 Highlights: First of its kind firecrackers with reduced PM & Ba emissions. Used multifunctional additives iron oxide and zeolite to reduce emissions. Conventional and REF tested inside FETC. PM and Ba emission reduction observed by 30–60%. Residue analysis revealed formation of heavy density particles.